ROLE OF FINE ART IN PRESERVING CULTURAL HERITAGE WITHIN RAPIDLY DEVELOPING URBAN AREAS IN DELTA STATE - Valentina Edna Owalegba OJIEH; Collins Oghenekome OJOH; Uchechukwu OGUM (International Studies Journal)
This study contributes to the field of cultural heritage preservation by critically exploring the underexplored significance of fine art in increasingly urbanising environments in Delta State, Nigeria. Unlike previous studies that have treated art primarily as aesthetic or symbolic, this study uses a multi-method approach qualitative interviews, visual analyses, and quantitative surveys to investigate how fine art functions as a medium for encoding, managing, and communicating cultural identity in three urban centres: Asaba, Warri, and Sapele. Through 399 survey responses and in-depth interviews with artists, urban planners, and cultural stakeholders, the study reveals a complex landscape in which only 34.09% of respondents perceive public art as linked to cultural identity, despite 89.97% acknowledging its potential for transmitting traditional values. Notably, the study identifies systemic barriers such as policy inaction, public disinterest, and funding limitations as critical impediments (R² = 0.975, *p* < 0.001), diverging from existing literature that emphasizes either community apathy or lack of infrastructure in isolation. By foregrounding participatory and site-specific art practices, particularly in Asaba and Sapele, this research contributes a novel analytical framework that situates fine art as an active agent in preserving intangible heritage amid urban change. It recommends culturally embedded art policies and enhanced community engagement as pathways to revitalizing heritage discourse in urban Nigeria.